17β-Estradiol Attenuates Hematoma Expansion Through Estrogen Receptor α/Silent Information Regulator 1/Nuclear Factor-kappa B Pathway in Hyperglycemic Intracerebral Hemorrhage Mice. Issue 2 (February 2015) - Zheng, Yun; Hu, Qin; Manaenko, Anatol; Zhang, Yang; Peng, Yan; Xu, Liang; Tang, Junjia; Tang, Jiping; Zhang, John H.
Abstract : Background and Purpose—: 17β-estradiol (E2) has been reported to reduce bleeding and brain injury in experimental intracerebral hemorrhage (ICH) model. However, it is not clear if E2 can prevent early hematoma expansion (HE) induced by hyperglycemia in acute ICH. The aim of this study is to evaluate the effects of E2 on HE and its potential mechanisms in hyperglycemic ICH mice. Methods—: Two hundred, 8-week-old male CD1 mice were used. ICH was performed by collagenase injection. 50% dextrose (8 mL/kg) was injected intraperitoneally 3 hours after ICH to induce acute HE (normal saline was used as control). The time course of HE was measured 6, 24, and 72 hours after ICH. Two dosages (100 and 300 μg/kg) of E2 were administrated 1 hour after ICH intraperitoneally. Neurobehavioral deficits, hemorrhage volume, blood glucose level, and blood–brain barrier disruption were measured. To study the mechanisms of E2, estrogen receptor α (ERα) inhibitor methyl-piperidino-pyrazole, silent information regulator 1 (Sirt1) siRNA was administered, respectively. Protein expression of ERα, Sirt1, and acetylated nuclear factor-kappa B, and activity of matrix metalloproteinases-9 were detected. Results—: Hyperglycemia enhanced HE and deteriorated neurological deficits after ICH from 6 hours after ICH. E2 treatment prevented blood–brain barrier disruption and improved neurological deficits 24 and 72 hours after ICH. E2 reduced HE by activating its receptor ERα, decreasing the expression of Sirt1, deacelylation of nuclear factor-kappa B, and inhibiting the activity of matrix metalloproteinases-9. ERα inhibitor methyl-piperidino-pyrazole and Sirt1 siRNA removed these effects of E2. Conclusions—: E2 treatment prevented hyperglycemia-enhanced HE and improved neurological deficits in ICH mice mediated by ERα/Sirt1/nuclear factor-kappa B pathway. E2 may serve as an alternative treatment to decrease early HE after ICH. Abstract : Supplemental Digital Content is available in the text.